Reversible femtosecond laser-assisted myopia correction: a non-human primate study of lenticule re-implantation after refractive lenticule extraction. - Andri K Riau (PLoS ONE, 2013)
LASIK (laser-assisted in situ keratomileusis) is a common laser refractive procedure for myopia and astigmatism, involving permanent removal of anterior corneal stromal tissue by excimer ablation beneath a hinged flap. Correction of refractive error is achieved by the resulting change in the curvature of the cornea and is limited by central corneal thickness, as a thin residual stromal bed may result in biomechanical instability of the cornea. A recently developed alternative to LASIK called Refractive Lenticule Extraction (ReLEx) utilizes solely a femtosecond laser (FSL) to incise an intrastromal refractive lenticule (RL), which results in reshaping the corneal curvature and correcting the myopia and/or astigmatism. As the RL is extracted intact in the ReLEx, we hypothesized that it could be cryopreserved and re-implanted at a later date to restore corneal stromal volume, in the event of keratectasia, making ReLEx a potentially reversible procedure, unlike LASIK. In this study, we re-implanted cryopreserved RLs in a non-human primate model of ReLEx. Mild intrastromal haze, noted during the first 2 weeks after re-implantation, subsided after 8 weeks. Refractive parameters including corneal thickness, anterior curvature and refractive error indices were restored to near pre-operative values after the re-implantation. Immunohistochemistry revealed no myofibroblast formation or abnormal collagen type I expression after 8 weeks, and a significant attenuation of fibronectin and tenascin expression from week 8 to 16 after re-implantation. In addition, keratocyte re-population could be found along the implanted RL interfaces. Our findings suggest that RL cryopreservation and re-implantation after ReLEx appears feasible, suggesting the possibility of potential reversibility of the procedure, and possible future uses of RLs in treating other corneal disorders and refractive errors.